(untitled) (Research, Society and Development, 2023)
Paget’s Disease of Bone (POD) has a viral and/or hereditary etiology, its strong familial component is noticeable, since 40% of patients have a family history of the disease, strengthening the idea that there is an autosomal dominant inheritance pattern. The main follow-up method used for patients with POP is the measurement of serum alkaline phosphatase, which is also used to assess the initial response to treatment. The purpose of this bibliographical study is to present, synthesize and describe the most relevant aspects that guide the medical follow-up of patients diagnosed with Paget’s Disease of Bone, in order to cite and analyze the importance of medical action in the care of these patients, in an attempt to generate knowledge and updates that help in dealing with these patients, above all, to avoid the evolution of the disease and the appearance of possible complications. UpToDate, Scielo, Virtual Health Library (VHL), PubMed and ebscohost were used as databases, using the following descriptors: Paget’s disease, laboratory monitoring, imaging tests, genetics and complications. The pagetic patient can evolve with osteosarcoma, irreversible hearing loss and paraplegia, making its multidisciplinary follow-up essential, through serum and bone alkaline phosphatase dosages, as well as the use of imaging tests, such as scintigraphy and radiography, for research of structural complications or neoplastic transformations, aiming at symptomatic relief along with delaying the progression of the disease, avoiding the total disability of the patient.